Compound heterozygous SZT2 mutations in two siblings with early-onset epilepsy, intellectual disability and macrocephaly. (March 2019) - Domingues, Francisco S.; König, Eva; Schwienbacher, Christine; Volpato, Claudia B.; Picard, Anne; Cantaloni, Chiara; Mascalzoni, Deborah; Lackner, Peter; Heimbach, André; Hoffmann, Per; Stanzial, Franco; Hicks, Andrew A.; et al.
Abstract: Purpose: Mutations in SZT2 have been previously reported in several cases of early onset epilepsy and intellectual disability. In this study we investigate potential causal mutations in two male siblings affected by early onset epilepsy, intellectual disability and macrocephaly. Methods: We use family-based whole-exome sequencing to identify candidate variants. Results: We report the identification of two potential causal SZT2 mutations in compound heterozygous state. We observe considerable differences in the clinical phenotype severity of the two affected individuals. The cerebral MRI revealed no abnormalities in the older affected brother, while in the youngest one it revealed a right frontal polymicrogiria. Moreover, while good seizure control was achieved in the older affected individual the younger brother is affected by pharmacoresistant epilepsy, progressive spastic paraplegia, cortical myoclonus and a more severe intellectual disability. We also analyzed the relative location of the reported pathogenic mutations in the SZT2 protein. Conclusion: Variable phenotypic expressivity is observed for this condition, while the location and type of mutations in SZT2 also has a potential impact on epilepsy severity. These findings extend our knowledge of epileptogenic conditions related to SZT2 and mTOR signaling.